Вибір критеріїв та розробка моделей для прогнозування фізико-хімічних властивостей ковшових шлаків при позапічній обробці чавуну - Степаненко, Д.О.; Вергун, О.С.; Кисляков, В.Г.; Руденко, О.Л.; Петруша, В.П.; Пушкаренко, М.В. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to the development of a methodology for the operational forecast of the properties of the final blast furnace slag by its chemical composition and temperature to improve the quality of hot metal in terms of sulfur content. The available information on the structure and properties of blast furnace slag, methods of their determination to establish the relationship between the parameters of the slag regime with blast furnace smelting parameters is studied and summarized, the dependence of the most important properties of blast furnace slag on its chemical composition and temperature is experimentally determined. To create predictive models, the method developed at the Iron and Steel Institute of Z.I. Nekrasov of the NAS of Ukraine used physico-chemical modeling to "convolve" information about the chemical composition of metallurgical melts, according to which the physico-chemical and structural state of slag melts is characterized by appropriate criteria. The analysis of the accumulated experimental data on the properties of modern blast furnace slags is performed, using the criteria of the theory of directed chemical bonding the dependences of liquidus temperature on model parameters are established and an adequate forecast model of bucket slag liquid temperature on its model parameters is obtained. The created technique allows to obtain temperature dependences of density, surface tension, viscosity and electrical conductivity of real blast furnace slags in the temperature range 1200–1400 °С. The approach to modeling of slag melts at the level of interatomic interaction used in the article can be used to develop predictive models of different technological properties of furnace slags in a wide range of temperatures. The obtained results are of practical importance and can be used for rapid prediction of the liquidity temperature of furnace slags and adjustment of their chemical composition in accordance with technological requirements.